Microgrids platform: A design and implementation of common platform for seamless microgrids operation - Kim, Jun Sung; So, Seong Min; Kim, Joong Tae; Cho, Jung Won; Park, Hee Jeong; Jufri, Fauzan Hanif; Jung, Jaesung (Electric Power Systems Research, 2019)
One of the main and essential features in microgrids is a reliable and secure communication networks which enable two-way communication between microgrids components and between microgrids to other systems. Microgrids components, as well as the other related system, currently work on different communication standards such as IEC 61850, Common Information Model (CIM), Open Platform Communication-Unified Architecture (OPC-UA), Modbus, and Distributed Network Protocol (DNP3). Therefore, it requires a harmonization system to enable them to communicate each other. This paper presents a development of a common platform for microgrids that provides interoperability between components with different communication standards. This common platform also provides necessary infrastructures to the various business owners who involve in the microgrids system. First, various communication standards used in the microgrids platform are described including the harmonization between particular standards. Then, the development of microgrids platforms including Substation Configuration Language (SCL) studio, SCADA, Integrated Model Harmonization Studio (IMHS), and integrated Gateway is presented. Finally, the conformity of the proposed microgrids platform is verified on IEEE 9-bus network.
Keywords: Common information model; Communication standards; IEC 61850; Micro grid; Open platforms; Common Information Model (CIM); Communication standard platform; IEC 61850; Microgrids; Open Platform Communication (OPC-UA)